Rejecting epiphobia - Baysan, E (Springer, 2020)
Epiphenomenalism denies some or all putative cases of mental causation. The view is widely taken to be absurd: if a theory can be shown to entail epiphenomenalism, many see that as a reductio of that theory. Opponents take epiphenomenalism to be absurd because they regard the view as undermining the evident agency we have in action and precluding substantial self-knowledge. In this paper, I defend epiphenomenalism against these objections, and thus against the negative dialectical role that the view plays in philosophy of mind. I argue that nearly in all cases where a theory implies one kind of epiphenomenalism, it is an epiphenomenalism of a non-problematic kind, at least as far as issues about agency and self-knowledge are concerned. There is indeed a problematic version of epiphenomenalism, but that version is not relevant to the debates where its apparent absurdity is invoked.